(3JWhjQ efgL GdMOjK GdfHhj GdTQja aj VhA ebGUO GdTQjYI GdESdGejI hCKQg aj JfejI GdhYj HgG dOi WdGH GdeQMdI GdKGfhjI GdCRgQjI (B/ s - (3YGOd Wg Cejf HcQjs; (3CMeO eMeO YjSi (B: s; (3Ydj CMeO eOchQ (B: s; (3eMeO dWaj eMeO LGO (B: s ((3GdbGgQI (B: s (3YGOd Wg Cejf HcQj (B: s, 2014)
(3JgOa GdOQGSI GdMGdjI Edi JWhjQ efgL GdMOjK GdfHhj GdTQja aj VhA ebGUO GdTQjYI GdESdGejI hCKQg aj JfejI GdhYj HgG dOi WdGH GdeQMdI GdKGfhjI GdCRgQjI(B: (3hbGFei ebGUO GdTQjYI GdESdGejI GdefGSHI dcd Ua OQGSj ef GdUaha GdKdGKI GdKGfhjI GdCRgQjI(B: (3hJMdjd eMJhi cJGH GdMOjK GdTQja hebjGS GdhYi hjTed ebjGS (B((3ebjGS GJLGg(B: (3hebjGS ehGba(B: (3hGNJHGQ JMUjdj(B) (3hPdc dJfejI GdhYi ai ebGUO GdTQjYI GdESdGejI(B: (3hJe JWHjb efgL eWhQ echf ef KdGK hMOGJ Ydi eLehYI ef WdGH GdUa GdKGfhi GdCRgQj hJchfJ GdYjfI ef (B42 (3WGdHG bSeJ Edi eLehYJjf(B: (3hCXgQJ GdfJGFL Cf GdefgL GdeWhQ dg JCKjQG cHjQkGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ GdJQHhjI (B- (3bSe GdefGgL hWQb GdJOQjS s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdMOjK GdTQja s; (3JWhjQ GdefGgL s; (3ebGUO GdTQjYIs